Chamber music - Jolivet, André 1905-1974 (ASV, 1996)
Petite Suite pour flûte, alto et harpe / Fantaisie-Caprice pour flûte et piano / Sonate pour flûte et piano / Sonatine pour flûte et clarinette / Alla rustica: Divertissement pour flûte et harpe / Suite en concert pour flûte et percussion.
Enth.: Petite suite. Fantaisie-caprice. Sonate for flute and piano (1958). Sonatine for flute and clarinet (1961). Alla rustica. Suite en concert for flute and four percussion (1965). - Interpr. u.a.: Noakes, Anna [Fl]. Sturrock, Kathron [Kl]. Tingay, Gillian [Hf]. Craven, Leslie [Klar]. Barritt, Jonathan [Va]. Cole, Graham [Schz]. Gledhill, Rachel [Schz]. Kettel, Gary [Schz]. Yates, Martin [Dir.].